IDENTIFIKASI KEBUTUHAN PUSAT SUMBER BELAJAR PADA SEKOLAH LANJUTAN PERTAMA DAN SEKOLAH LANJUTAN ATAS DI INDONESIA - Robinson Situmorang (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2006)
This research covering 30 junior High School in 10 regions in Indonesia aims at identifying the needs for learning resource center. the findings show that all schools have performed the funcion of learning resource center in instructional activities and 70% of the teachers has used media in their instructions; 78% of the schools have included learning resource center in their school stuctures; but only 30% of them treat the learning resource centers as formal organizations. more over, 90% of the schools provide special room for learning resource center which are generally used for Audio Visual. besides, the hardware and software of learning resources are not as complete as they should be. Based on the findings this research recomends the goverment facilitates the schools to develop learning resources center in each school as it has important and strategic roles in improving the quality of instructional process and competencies.